2019
DOI: 10.33224/rrch/2019.64.10.05
|View full text |Cite
|
Sign up to set email alerts
|

Modified graphite/graphene dot microsensors for the assay of trace amounts of lead and cadmium in water catchments areas using differential pulse anodic stripping voltammetry

Abstract: In this study, dot microsensors based on graphite/graphene paste modified with iron (II) phthalocyanine, nickel (II) phthalocyanine and 5,10,15,20-tetra(4pyridyl)21H, 23H porphine chloride tetrakis(methochloride) manganese(III) were used for the determination of trace amounts of lead and cadmium from various water catchments areas using differential pulse anodic stripping voltammetry. The response of the proposed dot microsensors were sensitive enough to detect very low levels of both metals ions in drinking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…5f) was obtained between 2.0 x 10 − 7 and 1.0 x 10 6 mol L 1 , with an LOD of 6.61 x 10 − 8 mol L − 1 and R = 0.9989, for n = 5. This LOD was comparable to recent studies of other electrode compositions 11,21 , but lower than that observed for some more expensive or non-usual materials [18][19][20][21][22] . However, GPUE-FA has the advantage of being composed of inexpensive and recycled materials, making it more nancially and environmentally friendly.…”
Section: Analytical Evaluationsupporting
confidence: 86%
See 1 more Smart Citation
“…5f) was obtained between 2.0 x 10 − 7 and 1.0 x 10 6 mol L 1 , with an LOD of 6.61 x 10 − 8 mol L − 1 and R = 0.9989, for n = 5. This LOD was comparable to recent studies of other electrode compositions 11,21 , but lower than that observed for some more expensive or non-usual materials [18][19][20][21][22] . However, GPUE-FA has the advantage of being composed of inexpensive and recycled materials, making it more nancially and environmentally friendly.…”
Section: Analytical Evaluationsupporting
confidence: 86%
“…In industry, cadmium is used in conjunction with nickel in rechargeable batteries, in pigments, deposited on various metals due to its resistance to corrosion, in alloys with other metals, and as impurity in the extraction of zinc 17 . There are many papers describing the use of different electrodes for the determination of Cd(II) in water 18,19 , the simultaneous determination of Cd(II) and Pb(II) in water [20][21][22] , herbal food supplements 23 , decorative materials 24 , hair 25 , bivalve mollusks 26 and paint 27 , among others. Other examples describe the simultaneous determination of Cd(II), Pb(II) and Cu(II) using modi ed glassy carbon in water 28 and parts of cigarettes 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some new electrochemical methods have been developed including glassy carbon electrodes with adsorbed nickel oxide. However, in 2019, Arnold-Tatu et al and van Staden et al published their work about utilization of unsubstituted iron(II) and nickel(II) phthalocyanines deposited on reduced graphene oxide and graphene paste, respectively [77,78]. The obtained modified electrodes were assessed in determination of lead and cadmium ions in water samples by using the coordination abilities of porphyrinoids.…”
Section: Detection Of Heavy Metals In Water Samplesmentioning
confidence: 99%